Centrilobular necrosis in autoimmune hepatitis: a histological feature associated with acute clinical presentation. Issue 3 (27th February 2006) - Hofer, H; Oesterreicher, C; Wrba, F; Ferenci, P; Penner, E
Abstract : Aims: The characteristic histological feature of autoimmune hepatitis (AIH) is interface hepatitis with predominant portal lymphoplasmacytic necroinflammatory infiltration. Centrilobular necrosis (CN), reminiscent of toxic or circulatory liver injury, has been reported in AIH. The aim of this study was to assess the frequency of CN in patients with AIH and its correlation with laboratory and clinical data. Methods: Liver biopsies were obtained from 114 patients (90 women, 24 men, mean (SD) age 45.4 (19.4) years) with AIH and were evaluated under code by a single pathologist according to the modified Knodell score. Results: CN was found in 20 (17.5%) patients with virtually unaffected portal areas in four cases. Patients with AIH with CN had a higher total hepatic activity index (median (range) 11 (6 to 15) v 5 (2 to 10)) and presented less frequently with cirrhosis (10% v 38%). Patients with CN had a higher frequency of acute onset (87% v 32%), higher bilirubin (median (range) 12.0 (0.43 to 40.0) v 1.9 (0.36 to 46)) and higher ALT levels (median (range) 25.6 (2.7 to 63.9) v 7.2 (0.7 to 62.6)), than did patients with AIH without centrizonal injury. Conclusion: CN with sparing of the portal areas represents a rare histological pattern in AIH. CN is associated with an acute clinical presentation and might reflect an early lesion preceding portal involvement. Recognition of this particular histological appearance enables early diagnosis of AIH and a timely initiation of immunosuppressive therapy.